Infrared thermography: A new approach for the characterization and management of activated carbons applied in water treatment. (31st December 2021) - Mariño Peacok, Thayset; Crespo Sariol, Harold; Yperman, Jan; Sánchez Roca, Ángel; Carleer, Robert; Puente Torres, Jeamichel; Adriaensens, Peter; Gryglewicz, Grazyna; Reggers, Guy; Czech, Jan; Vandamme, Dries; Salomón García, Liset
Graphical abstract: Highlights: A new non-invasive methodology using infrared thermography on activated carbon. An accurate analytical alternative for characterization and monitoring is discussed. Infrared thermography data correlate with exhaustion level of activated carbons. Infrared thermography results correlate with outcome of dedicated analytical methods. Infrared thermographic parameters correlate with surface area and pore volumes. Abstract: A new non-invasive methodology based on infrared thermography (IRT) to evaluate the exhaustion level of granular activated carbon (GAC) at different depths of a target industrial water treatment filter is studied. IRT results are discussed in terms of adsorption capacity and correlated with dedicated analytical methods: N2 gas adsorption, TGA, TD-GC/MS and NMR. Findings revealed that the surface temperature and surface thermal density parameters are contingent with the exhaustion level as well as the surface area and pore volumes of the GAC samples. Surface temperature decreased with 80% and the surface thermal density with 35% comparing exhausted Top-GAC and virgin GAC. Linear correlation was found between IRT parameters and the exhaustion profile of 98%. During GAC exploitation the surface area was reduced to 85% and the total volume of pore to 80%. The IRT method demonstrated to be simple and accurate and suitable for GAC management of water treatment.